The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Kiffe ta race - Binge Audio - Ly, Grace; Diallo, Rokhaya (Kiffe ta race - Binge Audio, 2018)
Pourquoi le mot « race » est-il tabou ? Qu’en est-il quand on est, à la fois, victime de discriminations raciales et sexuelles ? Comment assumer son identité plurielle ? Un mardi sur deux, Rokhaya Diallo et Grace Ly reçoivent un·e invité·e pour explorer les questions raciales sur le mode de la conversation et du vécu.
Le podcast continue en 2024 sur une nouvelle plateforme https://pseudo-radio.com/podcasts/kiffe-ta-race/
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; care; com5170; communication; corps; cours; discipline; europe; france; identités; intersectionnalité; journalisme; justice sociale; militance; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; théorie critique de la race; violences

Noires sous surveillance : esclavage, répression et violence d'État au Canada - Maynard, Robyn (Mémoire d'encrier, 2018)
La vérité a souvent un goût amer. Nous ne savons comment accepter nos histoires. Faut-il s’en tenir aux faits et dire la vérité ? Cet ouvrage monumental si richement documenté est précieux, il nous tire de l’oubli et du silence. Que savons-nous de l’esclavage au Canada ? Que savons-nous de la répression exercée sur les femmes et les hommes noirs ? Que savons-nous du racisme systémique ? Que savons-nous de la détresse des Autochtones, des sans-papiers, des personnes réfugiées ? Enfin fort peu… Parce que l’État construit et déconstruit les récits à travers les institutions. Les citoyen.ne.s sont ainsi condamné.e.s à reproduire une histoire qui nous échappe.
Donné en lecturecours FEM1000: "La misogynoire au Canada" p.173-178 Donné en lecture au cours POL4212: « Chapitre 5 : La Mysoginoire ».
Keywords: EDI; afro-féminisme; amériques; approches et analyses; canada; cours; discipline; discours dominant; fem1000; fem3300; féminismes noirs; histoire; justice sociale; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences